Main Model of Kurt Lewin's Change Management Based on Al-Quran Perspective - Berlian Telaumbanua; Nuri Aslami (Jurnal Fokus Manajemen, 2023)
At this time change is very essential and demanded in the world of organizations or companies. The main model of change management introduced by Kurt Lewin is something that must be explored again, in which he introduces a three-stage model which includes: Unfreeze-Change-Freeze. Companies can use this model as a reference and can be relied upon as an organization's success in transforming today. Therefore, a change management model introduced by Kurt Lewin is needed which is correlated based on the perspective of the Koran with the aim of this study so that new values are built both from the theoretical side put forward which is based on scientific studies and the religious side of the leadership style/model of change in organization. The method used in this research is a qualitative approach. This research was obtained using secondary methods and this research is based on literature from various kinds of literature books and scientific journals that strengthen the discussion of this research.